2013
DOI: 10.1111/ijd.12020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of community‐acquired methicillin‐resistant Staphylococcus aureus and antibiotic resistance in patients with atopic dermatitis in Porto Alegre, Brazil

Abstract: The results of this study confirm a high rate of S. aureus colonization in pediatric patients with AD and indicate a relevant association between colonization and high EASI score. No MRSA was found in cultures from this sample of patients in southern Brazil. Nearly one-third of isolates were identified as resistant to erythromycin, an antibiotic that is commonly used in pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
11
3
5
Order By: Relevance
“…In the current study, CA-MRSA was detected in 28 out of 54 patients colonized with S. aureus, while Hwang et al (2017) in Korea found that 39.4% of AD were colonized by MRSA. A lower percentage of MRSA among S. aureus isolates ranged from 0 to 16% in other reports (Petry et al 2014;Balma-Mena et al 2011;Suh et al 2008). This difference in the prevalence of S. aureus in AD patients might be due to variable methods of sampling, intermittent colonization, and the hygienic status of patients.…”
Section: Discussionmentioning
confidence: 69%
“…In the current study, CA-MRSA was detected in 28 out of 54 patients colonized with S. aureus, while Hwang et al (2017) in Korea found that 39.4% of AD were colonized by MRSA. A lower percentage of MRSA among S. aureus isolates ranged from 0 to 16% in other reports (Petry et al 2014;Balma-Mena et al 2011;Suh et al 2008). This difference in the prevalence of S. aureus in AD patients might be due to variable methods of sampling, intermittent colonization, and the hygienic status of patients.…”
Section: Discussionmentioning
confidence: 69%
“…It is well known that S. aureus colonizes skin in 60%–100% of AD patients as compared to 5%–30% of healthy controls 910111213. Moreover, 10%–30% of S. aureus isolated from AD patients shows methicillin-resistant S. aureus (MRSA), although there are variations according to areas and the prevalence of MRSA infection is increasing 131415161718. In this review, we discuss S .…”
Section: Introductionmentioning
confidence: 99%
“…In patients with AD, the prevalence of colonization of the skin and/or nose by S. aureus varies from 60 to 100 %, while in control subjects without AD it varies from 5 to 30 %. A correlation between bacterial colonization and severity of eczema has also been reported in the literature [ 61 ]. Some toxins produced by S. aureus act as superantigens: they are able to produce a massive activation of T cells and contribute to exacerbation of skin lesions.…”
Section: Topical Therapiesmentioning
confidence: 75%